2019
DOI: 10.1002/pssb.201900131
|View full text |Cite
|
Sign up to set email alerts
|

First‐Principles Calculations to Investigate the Refractive Index and Optical Dielectric Constant of Na3SbX4 (X = S, Se) Ternary Chalcogenides

Abstract: Ternary chalcogenides are promising candidate for visible light absorber as they have excellent optoelectronic properties. The ternary chalcogenides Na3SbX4 (X = S, Se) are investigated by using first‐principles calculations based on density functional theory (DFT). These chalcogenides have direct bandgap. The upper valence bands are predominantly composed of S or Se p‐orbitals and lower conduction bands consist of hybridization between Sb and S or Se p‐orbitals electrons. The optical absorption is investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The first principles are presented to investigate the adsorption reactions of gas sensor [10][11][12]. First principles are based on the fundamental theories of quantum mechanics, including density functional theory (DFT) calculations [13,14]. In [15][16][17], the structural, electronic and optical properties for compounds have calculated based on density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…The first principles are presented to investigate the adsorption reactions of gas sensor [10][11][12]. First principles are based on the fundamental theories of quantum mechanics, including density functional theory (DFT) calculations [13,14]. In [15][16][17], the structural, electronic and optical properties for compounds have calculated based on density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…Ternary chalcogenides show excellent dielectric properties and can be used for energy storage applications. Al-Douri et al reported that Na 3 SbX 4 ternary chalcogenide shows a direct bandgap and exhibits optical absorption. The dielectric functions of the material suggest its potential application as a superionic conductor.…”
Section: Introductionmentioning
confidence: 99%
“…The exchange correlation energy/potential functionals that are commonly used include the local spin density approximation (LSDA), the LSDA + USIC, the spin-Perdew–Burke–Ernzerhof generalized gradient approximation (PBE–GGA), the PBE–GGA + USIC, the PBESol, and the PBESol + U. The ternary arsenide zintl phases have strong electrical properties, mainly contributed by the As-p states calculated from the electronic structure combined with Boltzmann theory for transport phenomena using the pseudo-potential plane-wave method with GGA–PBEsol, which accurately predicted the equilibrium lattice and positional parameters. , Research on laves-phase PrFe 2 and PrRu 2 compounds exhibits superconductivity with critical temperatures of 550 and 580 K, respectively, calculated by using the GGA–PBESol + U approximation to address the f states of Pr atoms and the d states of Fe and Ru atoms . The lead halide double perovskites have demonstrated potential as a material for thermal conductivity at both high and low temperatures.…”
Section: Introductionmentioning
confidence: 99%